Critical Discourse Analysis of Moral Values in A Non-Governmental English Textbook for Junior High School Students - Octavia, Vika; Setyono, Budi; Ariyanto, Sugeng (English Education Study Program, 2023)
This study was conducted to investigate what and how moral values portrayed in a non-governmental EFL textbook for junior high school students for grade 8. The present study applied critical discourse analysis (CDA), framed in Fairclough’s three dimensional approaches to analyze visual, textual, and multimodal texts materials that represent the moral values in the textbook. The findings showed that Religiosity has the most frequently moral values found in the textbook, which is represented 36 times through different images, texts, and multimodal texts. Followed by the frequency of Nationalism and Helping each other took in a second place that represented moral values in the textbook, whereas the values of Integrity and Independence has the least frequently found in the textbook. Despite the potential imbalance in quantity, it can be inferred that this English textbook remains suitable for teaching the character education values to the students, since the textbook contains all five core moral values that recommended by the Indonesian government under the PPK program.